Denigrating and being denigrated for a higher end: Constructing ordinary expertise through supportive and belligerent talk. (September 2016) - Camauer, Leonor
Abstract: This article explores the construction of ordinary expertise as a joint venture between experts and advisees in a Swedish makeover television show aired since 2006, Lyxfällan (Eng. The Luxury Trap). This show is also an exponent of belligerent broadcasting (Higgins et al., 2012 ) and circulates a discourse of consumption which promotes an individualistic consumer ideal. Drawing on methodological approaches from studies of broadcast talk as talk-in-interaction and multimodal discourse analysis, the article examines the ways in which performances by advisers, advisees and an unseen narrator are made to work together to construct ordinary expertise. The analysis reveals that Lyxfällan׳ s construction of ordinary expertise heavily relies upon experts and advisees both following and breaking the general norms of ordinary conversations and the sociability of broadcast talk (Scannell, 1996 ), as well as the more specific conventions of the participation framework (Thornborrow, 2015 ) of exchanges between advisers and advisees. In following and breaking these norms and conventions, experts and advisees jointly construct ordinary expertise through the enactment of a dialectics of resistance and compliance, which in the end is tilted toward the advisers.